Depletion and Degradation Values in the Conventional Food Crop Sector of Malang Regency - Ittaqa Ramadhian Pranowo; Marlina Ekawaty (Journal of Development Economic and Social Studies, 2025)
Environmental issues alongside the looming climate crisis have developed into serious problems. ;Sustainable development lenses are becoming increasingly important in natural resource and environmental management decisions. Among other things, it relates to measuring the capacity of a resource and the changes in the environmental quality. Agriculture is one of the most vulnerable sectors. Broadly speaking, all types of agriculture are sensitive to changes in natural conditions. On the other hand, there is an increasing demand that accompanies population growth. Therefore the agricultural sector requires attention related to the application of a sustainable approach. Through this research, the costs incurred in the production through the form of; resource depletion and; environmental degradation have been calculated. As well as mapping the correlation that exists between the two. The research took a case study of the food crop sector in Malang District over the period of 2018-2023. The research then shows the findings that the conventional food crop sector in Malang District has caused an impact on depletion and degradation. Meanwhile a positive correlation was found between the two. However, it is considered at a very weak level of closeness. The results of this study provide information and reference on the state of depletion and degradation in the food crop sector.